2019
DOI: 10.21037/tlcr.2019.04.14
|View full text |Cite
|
Sign up to set email alerts
|

Molecular testing strategies in non-small cell lung cancer: optimizing the diagnostic journey

Abstract: Molecular testing identifies patients with advanced non-small cell lung cancer (NSCLC) who may benefit from targeted therapy or immunotherapy (i.e., immune checkpoint inhibitor treatment for patients with high tumor mutational burden (TMB), microsatellite instability-high or mismatch repairdeficient tumors). Current guidelines state that molecular testing should be conducted at the time of initial diagnosis and tumor progression on targeted therapy. In real-world clinical practice in the United States (US), mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 77 publications
1
69
0
Order By: Relevance
“…As the leading cause of cancer‐related deaths worldwide, lung cancer is categorized into non‐small cell lung cancer (NSCLC) and small cell lung cancer with the former occupying 85% of all lung cancer cases . Since the initial presentation, NSCLC patients undergo multiple clinical and molecular examinations before implementation of treatment including clinical work‐up, biopsy, and molecular testing, and apart from surgery, platinum‐based chemotherapy, target therapy, and the novel immune therapy are administered accordingly . Although NSCLC is no longer incurable after decades of efforts, it is still premature to say that its prognosis is satisfying.…”
Section: Introductionmentioning
confidence: 99%
“…As the leading cause of cancer‐related deaths worldwide, lung cancer is categorized into non‐small cell lung cancer (NSCLC) and small cell lung cancer with the former occupying 85% of all lung cancer cases . Since the initial presentation, NSCLC patients undergo multiple clinical and molecular examinations before implementation of treatment including clinical work‐up, biopsy, and molecular testing, and apart from surgery, platinum‐based chemotherapy, target therapy, and the novel immune therapy are administered accordingly . Although NSCLC is no longer incurable after decades of efforts, it is still premature to say that its prognosis is satisfying.…”
Section: Introductionmentioning
confidence: 99%
“…These subclones can have distinct morphological and genetic features, including a different ALK status, and may further evolve, independent of or in response to therapies such as ALK inhibition. This phenomenon has an important practical implication, i.e., that tumor specimens collected from different anatomic sites or even the same anatomic site but at different time points in a lung cancer patient may need to be tested for ALK status [ 9 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple assays that have been developed and applied for the assessment of ALK status, including fluorescence in situ hybridization (FISH), immunohistochemistry (IHC), polymerase chain reaction (PCR) and reverse-transcription PCR (RT-PCR) assays, and next generation sequencing (NGS)-based DNA sequencing (DNA-seq) and RNA sequencing (RNA-seq) technologies. In numerous studies, improvements and optimization of these assays, rational diagnostic algorithms utilizing some or all these assays, and potential causes and solutions for the discrepant results obtained by different assays [ 9 , 10 , 11 , 12 ] have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to provide individualized precise treatment and to predict tumor response to immunotherapy ( Madore et al, 2015 ; Kaunitz et al, 2017 ; Sui et al, 2018 ; Liu and Wu, 2019 ). To fulfill the need for real-time monitoring, the analysis of liquid biopsy-based circulating biomarkers is preferred ( Nishino et al, 2013 ; Ando et al, 2019 ; Gregg et al, 2019 ; Kloten et al, 2019 ; Tang et al, 2020 ). Recent studies demonstrated that melanoma patients who were less responsive to anti-PD-1 blockade had a significantly higher level of circulating ExoPD-L1 prior to treatment as compared with responders ( Chen G. et al, 2018 ).…”
Section: Potential Clinical Implication Of Circulating Exopd-l1 As a mentioning
confidence: 99%